Diagnosis of EFL Learners’ Difficulties in the Use of Connectors in a writing task: Strategies for Remedial Work - Jiménez Catalán, Rosa Mª; Ojeda Alba, Julieta (Didáctica. Lengua y Literatura, 2019)
Connectors are words that serve to join other words, phrases, and clauses together. They range from single words to combination of words, as well as adverbs serving conjunctive functions in the sentence. Connectors are very important for language teachers and learners, as they structure texts in discourse and, as a result, they have considerable influence on learners’ success or failure in communication in a target language. However, they have been traditionally neglected in ELT coursebooks, particularly in beginners and intermediate levels; this may explain the many difficulties learners encounter when writing texts as reported in Granger & Tyson (1996), Abe (2001), Lee (2003), Fe (2006), Wei-Yun Chen (2006), Zhang (2007), Bikeliené (2008), Jalilifar (2008), Jiménez Catalán & Ojeda Alba (2010). The aims of this paper are twofold. Firstly, we identify patterns of connector misuse in a wide collection of examples drawn from a corpus of written essays by 228 Spanish learners of English in secondary education. Secondly, we propose strategies for remedial work for basic to intermediate levels. Our results show three types of problems with English connectors: total omission and scarcity of connectors, addition of unnecessary connectors, and wrong choice of connectors. On the basis of the difficulties diagnosed we include some guidelines for remedial work as well as examples of tasks that may help EFL learners develop explicit and implicit knowledge of the use of connectors in written texts.